1993
DOI: 10.2169/internalmedicine.32.806
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complex Glomerulonephritis in a Pregnant Woman with Congenital C9 Deficiency.

Abstract: A 27-year-old womandeveloped proteinuria, hypertension, and peripheral edema during the ninth monthof her first pregnancy. The clinical and serological features were compatible with a diagnosis of toxemia of pregnancy, except for the presence of hypocomplementemia. The patient had glomerulonephritis characterized by large electron-dense deposits, predominantly in the mesangium. Immunofluorescence studies revealed striking accumulations of Clq and C3, and the presence of small amounts of IgG and IgM in the mesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Indeed, the percentage of C9D among patients with mesangial proliferation and duplication of GBM in this study was 5.1%, which is higher than the estimated frequencies of C9D in the general population in Japan (0.12%). In addition to the two cases in this study, previously reported adult C9D cases with IgAN also exhibited partial membranoproliferative lesions [4]. Some investigators suggested that complement deficiency predisposes the individual to chronic infections and subsequent immune complex formation, and impairs the solubilization, disaggregation and clearance of deposited immune complexes [16].…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Indeed, the percentage of C9D among patients with mesangial proliferation and duplication of GBM in this study was 5.1%, which is higher than the estimated frequencies of C9D in the general population in Japan (0.12%). In addition to the two cases in this study, previously reported adult C9D cases with IgAN also exhibited partial membranoproliferative lesions [4]. Some investigators suggested that complement deficiency predisposes the individual to chronic infections and subsequent immune complex formation, and impairs the solubilization, disaggregation and clearance of deposited immune complexes [16].…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, several case reports have described patients with C9D and glomerulonephritis including IgAN [4][5][6][7]. Alexopoulos et al [10] showed no correlation among glomerular T cells, monocytes/macrophages and the deposition of C5b-9.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations